2005
DOI: 10.1159/000084162
|View full text |Cite
|
Sign up to set email alerts
|

Basal Prolactin Values Correlate with Response to Reboxetine Treatment in Major Depression, but Not with Response to Citalopram

Abstract: Little is known about variables that might predict outcome in major depression. Recently, basal prolactin values (BPV) have been suggested to predict response to treatment with tricyclic antidepressive drugs. In order to examine whether BPV predict response to selective mono-aminergic therapy, 24 in-patients with major depression were treated in a single-masked, randomised study using the most selective noradrenergic or serotonergic reuptake inhibitors available for antidepressant treatment, i.e. reboxetine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
2
0
3
Order By: Relevance
“…One explanation may be that DA levels are higher in these brain areas and may lead to hypoprolactinemia, which has been associated with depressive behavior (Moeller et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One explanation may be that DA levels are higher in these brain areas and may lead to hypoprolactinemia, which has been associated with depressive behavior (Moeller et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, basal prolactin levels have been reported to be predictive for response to reboxetine treatment in major depression, but not for response to citalopram [5]. It has also been reported that antidepressants which selectively modify noradrenergic function also have effects on serotonin function, as measured by neuroendocrine testing, since after 6 weeks of treatment they increase serotonin-mediated cortisol response to D-fenfluramine, a specific 5-HT releasing agent without the catecholamine effects [6].…”
Section: Discussionmentioning
confidence: 99%
“…Zum einen ist sowohl die selektive Rückaufnahme von Serotonin [20][21][22] wie auch von Noradrenalin [22,23] antidepressiv wirksam: Auch wenn im Einzelnen Serotonin und Noradrenalin zu differentiellen Effekten im Zentralnervensystem (ZNS) führen [24][25][26], ist die antidepressive Wirksamkeitalsonichtexklusiv mit einem einzelnen Monoamin verknüpft.…”
Section: Antidepressivaunclassified